1992
DOI: 10.1093/ajh/5.7.423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enalapril on the Progression of Chronic Renal Failure

Abstract: In order to study the influence of angiotensin converting enzyme (ACE) inhibition on the progression of chronic nephropathy, 70 patients with a median glomerular filtration rate (GFR) of 15 (range, 6 to 54) mL/min/1.73 m2 were randomized in an open study to basic treatment with enalapril or conventional antihypertensive treatment. The patients were followed for at least 2 years or until they needed dialysis. The groups were comparable with respect to age and sex distribution, etiology of renal diseases, initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(66 citation statements)
references
References 0 publications
2
64
0
Order By: Relevance
“…Many clinical studies have shown the beneficial effects of ACEI on delaying the progression of kidney disease (5)(6)(7)(8). This has led to the widespread use of ACEI in patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical studies have shown the beneficial effects of ACEI on delaying the progression of kidney disease (5)(6)(7)(8). This has led to the widespread use of ACEI in patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…AngII also stimulates cell proliferation and tissue remodeling by enhancing the synthesis of profibrotic cytokines and growth factors, among these, TGF-␤1 (3,4). Because the RAAS has an important role in renal pathophysiology, agents that inhibit this system, such as angiotensin-converting enzyme inhibitor (ACEI) or AngII receptor 1 blocker, have been shown to have beneficial effects in patients with CKD (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Since the RAAS has an essential role in both renal as well as cardiovascular pathophysiology, agents that inhibit this system such as angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs), have been shown to have beneficial effects in patients with both chronic renal and cardiovascular diseases (17,24,31,37,43). Angiotensin II also activates NADPH oxidase, inducing oxidative stress in both the renal and cardiovascular systems by inducing free radical generation (1,57), specifically, reactive oxygen species (ROS).…”
mentioning
confidence: 99%
“…[22][23][24] Oxidative stress and inflammation are implicated in both renal and cardiovascular diseases. 25,26 In hypertension, renal iNOS expression can be augmented in response to an increment in ROS.…”
Section: Discussionmentioning
confidence: 99%